Práticas de docentes de psicologia sobre a formação e atuação em psicologia social comunitária - Giesel, Gisele Groehler (2018)
The present study aimed to identify and analyze the practices of teachers of Psychology courses regarding the training of students to work in Community Social Psychology. Semi-structured interviews were carried out with twelve teachers, from Psychology courses, from private higher education institutions that teach disciplines with the focus of Community Social Psychology in the City of Curitiba-Pr. The results showed that the subjects are taught based on the course syllabus, the teachers select the contents and use a variety of didactic resources (books, articles, newspapers, videos) and active methodologies. The learning assessment strategies are also diversified (evidence, dynamics, seminars), which constitutes a procedural evaluation. Supervised internships are conducted at different health and social care institutions, directed toward practices consistent with the principles of CSP. The teachers have experience in the area of the PSC and perceive that it represents an expanding field, and that the educational institutions are recognizing the advances of this area of action, so they seek to articulate theory and practice from a psychosocial perspective. In view of these results, the importance of continuing education and teacher qualification is highlighted, given the fact that these factors are fundamental in the exercise of the profession and training of future professionals in the area of Community Social Psychology.